2019
DOI: 10.1080/09640568.2019.1679615
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of non-timber forest products to the livelihood of farmers in coffee growing areas: evidence from Yayu Coffee Forest Biosphere Reserve

Abstract: This paper examines the role of forest products in the livelihoods of forest-dependent households in the Yayu Coffee Forest Biosphere Reserve in the South Western part of Ethiopia. Unlike many forest landscapes, households in Yayu district cultivate their primary crop, coffee, in a complex landscape. Sampled households (n=241) were chosen based on stratified random sampling method. We employ both descriptive statistics and econometric regression to assess the extent of forest products use and analyse the deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…Contribution of forest products and wild foods from non‐forest environments in household food; nutritional security and income generation have been widely discussed (Angelsen et al, 2014; Beyene et al, 2019; Broegaard et al, 2017). Bakkegaard et al (2017) argue that the mean incomes from forest and wild products exceed the mean agricultural income.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Contribution of forest products and wild foods from non‐forest environments in household food; nutritional security and income generation have been widely discussed (Angelsen et al, 2014; Beyene et al, 2019; Broegaard et al, 2017). Bakkegaard et al (2017) argue that the mean incomes from forest and wild products exceed the mean agricultural income.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these key attributes, many people, particularly in the developing countries, depend on them in the times of acute food shortage after occurrence of hazards such as drought and bad harvests. As they are more obliged to prepare household meals, women in rural and urban areas particularly those stricken with poverty tend to revert WEPs utilization when there is shortfall in household income (Beyene et al, 2019; Fikir et al, 2016). WEPs can be important to the coming age (young people leaving their homes and establishing homesteads), as coming age as they are likely more energetic to conduct forest activities (Harrison, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Agroforestry plantation systems (e.g. cocoa, coffee), besides improving productivity (Pinard et al 2014), are also found to contribute to farmers' livelihoods by providing NTFPs (Beyene et al 2019). Some studies reminded of the potential benefits that value chain improvements (Deans et al 2018), greening (Nhantumbo and Camargo 2016) and certification (Millard 2011;Mitiku et al 2018) of agroforestry plantations could bring for local communities, such as price premiums or improved benefit sharing.…”
Section: Agroforestry Systemsmentioning
confidence: 99%
“…As with traditional forestry, evidence shows that overexploitation of natural resources is leading to their depletion, which points to the need for sustainable management and cultivation, for the sake of both natural resources and forest-dependent communities' livelihoods (Dovie 2003;Kimaro and Lulandala 2013). Indeed, the contribution of NTFPs to household income was shown to be important, particularly for poorer and/or more remote households, who also use them to fulfill their basic needs (Heubach et al 2011;Malleson et al 2014;Schaafsma et al 2014;Beyene et al 2019). They represent an income equalizer and an opportunity for poverty alleviation in rural areas, as well as contributing to food security and resilience in time of crisis.…”
Section: Subsistence and Income Diversification Through Forest-based mentioning
confidence: 99%